A rare case report: acute necrotizing encephalopathy and acute fulminant myocarditis - Juan Ma; Chenliang Pan; Nan Bai; Shanshan Zhang; Peiling Mi; Yongling Wa; Andong Lu (Frontiers in Cardiovascular Medicine)
BackgroundAcute necrotizing encephalopathy (ANE) is a rare condition characterized by multiple symmetrical brain lesions mainly involving the thalamus. Acute fulminant myocarditis is a diffuse inflammatory disease of the myocardium characterized by acute onset, rapid progression, and a high risk of death. Its pathogenesis involves excessive activation of the innate immune system and the formation of an inflammatory storm. Both conditions are thought to be caused by viral infections. We present a case of ANE with fulminant myocarditis. Reporting this case is important due to the rarity and the critical interplay of these two severe conditions occurring simultaneously.Case presentationA 16-year-old student presented with a 3-day history of high fever, cough, and expectoration, followed by multiple episodes of convulsive seizures. Despite high doses of vasoactive medications, the patient exhibited low blood pressure and elevated lactate levels. Portable echocardiography revealed diffuse decreased left ventricular motion with severe left ventricular dysfunction (ejection fraction < 30% by visual estimation). The patient was diagnosed with acute fulminant myocarditis. The patient remained comatose with a Glasgow coma scale (GCS) score of 3 (E1VeM1). Brain CT and MRI revealed bilateral striatal, thalamic, and brainstem lesions, typical of ANE. Consequently, a diagnosis of ANE accompanied by fulminant myocarditis was considered. The treatment regimen included high doses of glucocorticoids, immunoglobulins, tocilizumab, and V-A ECMO (Veno-arterial extracorporeal membrane oxygenation) life support. The patient showed significant recovery of cardiac function and was discharged after approximately 24 days of rehabilitation.ConclusionThis case report highlights the coexistence of ANE and fulminant myocarditis. The underlying mechanisms remain unclear. Early recognition of these two conditions is crucial for prognosis, though challenging. This report underscores the need for heightened awareness and prompt, comprehensive treatment strategies to improve outcomes in such complex cases.